In search of lost time: raman thermochronology of FC-1 zircon - Härtel, Birk; Enkelmann, Eva; Jonckheere, Raymond; Ludwig, Thomas; Krause, Joachim; Ratschbacher, Lothar (Contributions to mineralogy and petrology, 2024)
Translating thermochronological ages to geological models requires knowledge of the thermal sensitivity of the applied thermochronometer, i.e. the closure temperature or the partial annealing/retention zone. Zircon Raman dating is a thermochronometer that uses radiation-damage measurements and matched analyses of actinide contents in zircon. Experimental work placed its closure temperature at 330-370 degrees C for the internal nu(2)(SiO4) and nu(3)(SiO4) Raman bands at 439 and 1008 cm(-1), and 260-310 degrees C for the external rotation (ER) band at 356 cm(-1). However, experimental annealing models also predict partial radiation-damage annealing over a broad temperature range (> 500 degrees C). We test these closure temperatures by dating zircon from the U-Pb reference material FC-1. We matched Raman-based radiation-damage measurements with U and Th concentrations measured with a secondary ion mass spectrometer. The zircon Raman ages for the nu(2), nu(3), and ER bands are 942 +/- 23 Ma (2 s), 978 +/- 38 Ma, and 1033 +/- 32 Ma. This is lower than the expected range of 1040-1080 Ma, between the apatite U-Pb (similar to 490 degrees C) and zircon (U-Th)/He (ZHe; similar to 200 degrees C) ages. We discuss long-term, low-temperature annealing of radiation damage during protracted cooling of the sample as a cause of age reduction. This explanation fits both, experimental annealing models and zircon Raman data from other geological settings. Long-term, low-temperature annealing complicates the interpretation of standalone zircon Raman data. However, exploiting this effect by combining zircon Raman and ZHe dating on the same sample provides thermal-history information beyond that revealed by either of them.